Biology Reproduction and Dynamic of Gonads Maturity Blue Swimming Crabs (Portunus pelagicus) in Betahwalang Waters, Demak - Sri Redjeki; Muhammad Zainuri; Ita Widowati; Abdul Ghofar; Elsa Lusia Agus; Mustagpirin Mustagpirin; Panji Ayodya (Universitas Diponegoro, 2020)
The waters of Betahwalang, Demak has quite potential fisheries resources. For the sustainability of crab resources, active management is necessary applied. Information on biology reproduction of crabs is required. The purpose of this research was to determine the biological aspects of sex ratio and the dynamics of the gonadal maturity level. This research was conducted on September-November 2018 in Betahwalang Waters. The method used in this study is a descriptive research method. Data were collected by determining gender, weight and width of the carapace, the level of gonadal maturity. The results from observations of crab landed with a total of 6,292 crabs showed a percentage of 37.30% males and 62.70% females with sex ratios in September (1: 1.70), October, (1: 1.46), and November (1: 1.98). The observation of gonadal maturity level in September (Level I 162 crabs, Level II 1425 crabs, Level III 607 crabs) in October (Level I 130 crabs, Level II 832 crabs, Level III 207 crabs), and in November (Level I 46 crabs, Level II 753 crabs, Level III 195 crabs). The results show that the average crab catch on Betahwalang waters is dominated by the gonad II maturity level reaching (> 70%) of the total female caught. The results of the gonad maturity level are influenced by weather and season factors where the trend of the gonad maturity level will drop in the rainy season or in November.